2016
DOI: 10.3389/fneur.2016.00199
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the NG2 Glial Scar after Spinal Cord Injury

Abstract: NG2 cells, also known as oligodendrocyte progenitor cells, are located throughout the central nervous system and serve as a pool of progenitors to differentiate into oligodendrocytes. In response to spinal cord injury (SCI), NG2 cells increase their proliferation and differentiation into remyelinating oligodendrocytes. While astrocytes are typically associated with being the major cell type in the glial scar, many NG2 cells also accumulate within the glial scar but their function remains poorly understood. Sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(68 citation statements)
references
References 128 publications
1
67
0
Order By: Relevance
“…After CNS injury, NG2-OPCs are present in two compartments, scar borders and spared reactive neural tissue ( Figure 1A and Figure 3A). In scar borders, NG2-OPCs are hypertrophied and are reported to restrict axon dieback and axon regrowth (68)(69)(70). Other reports show that robust axon growth can…”
Section: R E V I E W S E R I E S : G L I a A N D N E U R O D E G E N mentioning
confidence: 99%
“…After CNS injury, NG2-OPCs are present in two compartments, scar borders and spared reactive neural tissue ( Figure 1A and Figure 3A). In scar borders, NG2-OPCs are hypertrophied and are reported to restrict axon dieback and axon regrowth (68)(69)(70). Other reports show that robust axon growth can…”
Section: R E V I E W S E R I E S : G L I a A N D N E U R O D E G E N mentioning
confidence: 99%
“…Several developmental signals have been found to be upregulated in the glial scar that promote NG2 glial proliferation and migration to trauma sites: fibroblast growth factor (FGF), platelet-derived growth factor (PDGF), Wnts 27 . However, many NG2 glia in the scar do not differentiate into myelinating oligodendrocytes.…”
Section: Functional Diversity Of Glial Cells In the Injured Cnsmentioning
confidence: 99%
“…Could it also be possible that NG2-glia regulate responsiveness of other cell types in acute stress? Indeed, in animal models of demyelination and CNS injury, several reports demonstrated that NG2-glia cells secrete a variety of pro-inflammatory chemokines and cytokines in pathological conditions that can dampen the glial or neuronal compensation machinery [113,114]…”
Section: Association Of Ng2-glia With Neuropsychiatric Disordersmentioning
confidence: 99%